IMPACTS OF CULTURAL TOURISM IN PAKISTAN - Rabia Hayat , Muhammad Asif , Maria Riaz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this study is to find out the culture tourism positive and negative impacts in Pakistan, and how to overcome these negative impacts and promoting the positive impacts, and whose policies are adopts that are these best managed. Cultural tourism is the act of travelers visiting particular destinations in order to experience and learn about a particular culture. This can include many activities such as; attending events and festivals, visiting museums and tasting the food and drinks. The research will be descriptive in nature qualitative technique would be applied in this study. The methods of data collection would be archival research mainly primary documents and secondary document. Due to this situation negative impacts emerged hybrid culture and Acculturation affects .and Positive impacts improvements the local communities, economic condition, social conditions and developed cultural understanding.